Technology and Its Impact on Education - Mohamad Joko Susilo; Dwi Sulisworo; Suhairee Beungacha (Buletin Edukasi Indonesia, 2023)
Technology and education are two sectors that are continuously developing side by side. They support the integrated development of other sectors to encourage the progress of human civilization. However, in order to keep up with the new generation's technological advancements, the ways of educating need to be reconsidered. This literature review aims to explain the impact of technology on education. Data obtained from various literature sources, especially journals, were analyzed using qualitative analysis consisting of data reduction, data display, and drawing conclusions. Based on the results, it was found that the sustainability of values transmission occurs through the education process, making the integration of technology with contextual learning very important. Educators, as the closest people responsible for the learning process, need to constantly improve their abilities to provide the best learning environment for students by using various easily accessible learning resources.